2020
DOI: 10.1111/bjd.19345
|View full text |Cite
|
Sign up to set email alerts
|

Global Hidradenitis Suppurativa COVID‐19 Registry: a registry to inform data‐driven management practices

Abstract: alveolar capillaries, 2 endothelial cells of kidney glomeruli, 3 brain blood vessels, 4 colonic mucosa 5 and skin. 6 Our immunohistochemical study represents a straightforward means of linking SARS-CoV-2 infection and endothelium.The presence of the virus in eccrine glands suggests sweat as a source of contagion, but this should be interpreted with caution. Given the similarities of SARS-CoV and SARS-CoV-2, it is worth mentioning that in a 2004 study of four autopsied patients with SARS, Ding et al. 7 found SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…Thus, additional research is needed to overcome racial or ethnic disparities and small sporadic reports from across the world. Dermatologists around the world can work together to build case registries to overcome the small sample sizes of dermatological patients with COVID‐19 to inform evidence‐based management practices during the COVID‐19 pandemic 41–43 . In addition, even if the skin disease itself does not increase the susceptibility to SARS‐CoV‐2 infection, in order to reduce potential exposure of dermatological patients to patients with COVID‐19, it is necessary to reduce nonurgent outpatient visits and consider telemedicine during the COVID‐19 pandemic 42,44 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, additional research is needed to overcome racial or ethnic disparities and small sporadic reports from across the world. Dermatologists around the world can work together to build case registries to overcome the small sample sizes of dermatological patients with COVID‐19 to inform evidence‐based management practices during the COVID‐19 pandemic 41–43 . In addition, even if the skin disease itself does not increase the susceptibility to SARS‐CoV‐2 infection, in order to reduce potential exposure of dermatological patients to patients with COVID‐19, it is necessary to reduce nonurgent outpatient visits and consider telemedicine during the COVID‐19 pandemic 42,44 …”
Section: Discussionmentioning
confidence: 99%
“…Dermatologists around the world can work 12 (0Á2) 0 1Á00 Biologics TNF-a inhibitors 3 (0Á04) 0 1Á00 0 3 (0Á04) 1Á00 3 (0Á04) 0 1Á00 3 (0Á04) 0 1Á00 Etanercept 1 (0Á01) 0 1Á00 0 1 (0Á01) 1Á00 1 (0Á01) 0 1Á00 1 (0Á01) 0 1Á00 Infliximab 1 (0Á01) 0 1Á00 0 1 (0Á01) 1Á00 1 (0Á01) 0 1Á00 1 (0Á01) 0 1Á00 Adalimumab 1 (0Á01) 0 1Á00 0 1 (0Á01) 1Á00 1 (0Á01) 0 1Á00 1 (0Á01) 0 together to build case registries to overcome the small sample sizes of dermatological patients with COVID-19 to inform evidence-based management practices during the COVID-19 pandemic. [41][42][43] In addition, even if the skin disease itself does not increase the susceptibility to SARS-CoV-2 infection, in order to reduce potential exposure of dermatological patients to patients with COVID-19, it is necessary to reduce nonurgent outpatient visits and consider telemedicine during the COVID-19 pandemic. 42,44 This study showed that patients with various dermatological diseases or exposure to biologics were not particularly susceptible to COVID-19 and did not have worse outcomes of COVID-19 compared with others.…”
Section: Discussionmentioning
confidence: 99%
“…There has been some debate on whether patients with HS would have an increased risk of severe COVID because of an overlap between comorbidities associated with HS and prognostic factors of COVID‐19 2 . An international registry has been developed in an attempt to collect more comprehensive data on HS severity, therapy and COVID‐19 outcomes 3 . There has also been concern regarding potential racial disparities affecting COVID outcomes 2,4 .…”
Section: Total (N = 39) Not Hospitalized (N = 31) Hospitalized (N = 8mentioning
confidence: 99%
“…41,42 Many medical specialties have already invested into developing COVID-19 patient registries. [43][44][45][46] Although they are useful for research, patient registries outside the EHR system have limited capacity to receive real-time data of patients. A large regional public academic health center used rapid EHR configurations to manage COVID-19 that incorporated some of the features of our effort.…”
Section: Discussionmentioning
confidence: 99%